An experimental investigation of the effect of thermal coupling between parallel microchannels undergoing boiling on the Ledinegg instability-induced flow maldistribution. (June 2021) - Miglani, Ankur; Weibel, Justin A.; Garimella, Suresh V.
Highlights: Effect of thermal coupling between parallel microchannels on Ledinegg instability-induced flow maldistribution is studied Thermal coupling is shown to reduce the wall temperature difference between the channels and dampen flow maldistribution Thermal coupling reduces the range of input powers with non-uniform flow and the maximum severity of flow maldistribution Role of thermal coupling in dampening flow maldistribution is confirmed via agreement between model and experiments Abstract: Two-phase flow boiling is susceptible to the Ledinegg instability, which can result in non-uniform flow distribution between parallel channels and thereby adversely impact the heat transfer performance. This study experimentally assesses the effect of thermal coupling between parallel microchannels on the flow maldistribution caused by the Ledinegg instability and compares the results to our prior theoretical predictions. A system with two parallel microchannels is investigated using water as the working fluid. The channels are hydrodynamically connected via common inlet/outlet plenums and supplied with a constant total flow rate. The channels are uniformly subjected to the same input power (which is increased in steps). Two separate configurations are evaluated to assess drastically different levels of thermal coupling between the channels, namely thermally isolated and thermally coupled channels. Synchronized measurements of the flow rate in each individual channel, wall temperature, and pressure drop are performed along with flow visualization to compare the thermal-hydraulic characteristics of these two configurations. Thermal coupling is shown to reduce the wall temperature difference between the channels and dampen flow maldistribution. Specifically, the range of input power over which flow maldistribution occurs is noticeably smaller and the maximum severity of flow maldistribution is reduced in thermally coupled channels. The data provide a quantitative account of the effect of lateral thermal coupling in moderating flow maldistribution, which is corroborated by comparison to the predictions from our two-phase flow distribution model. This combined experimental and theoretical evidence demonstrates that, under extreme conditions when one channel is significantly starved of flow rate and risks dryout, channel-to-channel thermal coupling can redistribute the heat load from the flow-starved channel to the channel with excess flow. Due to such a possibility of heat redistribution, the coupled channels are significantly less prone to flow maldistribution compared to thermally isolated channels.